THE GENUS MURICOCOCCUM Chun & How (Euphorb.) - A.J.G.H KOSTERMANS (Research Center for Biology, 1961)
The monotypical genus Muricococcum was published in 1956 (in Acta Phytotaxonomica Sinica 5: 14) with a latin and Chinese diagnosis.